2018
DOI: 10.1016/j.clinph.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Cortical inhibitory function in cervical dystonia

Abstract: These results clarify the nature of deficits in cortical inhibitory function in dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
5
12
0
Order By: Relevance
“…Our results of elevated visual and visualtactile TDTs support the hypothesis of TDT accounting as an endophenotype 1 . Furthermore, our results are in line with other studies, that did not find group differences for tactile TDT in CD 5,6 , indicating that tactile TDT is not as sensitive as visual-tactile TDT. The existence of controversial study results concerning TDT modalities could be partly due to methodical differences, the number of patients, and the way of data analyses, as reporting of combined TDTs, mean TDT on group level or Z scores with percentages of altered TDTs within patient groups 2,5-7 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results of elevated visual and visualtactile TDTs support the hypothesis of TDT accounting as an endophenotype 1 . Furthermore, our results are in line with other studies, that did not find group differences for tactile TDT in CD 5,6 , indicating that tactile TDT is not as sensitive as visual-tactile TDT. The existence of controversial study results concerning TDT modalities could be partly due to methodical differences, the number of patients, and the way of data analyses, as reporting of combined TDTs, mean TDT on group level or Z scores with percentages of altered TDTs within patient groups 2,5-7 .…”
Section: Discussionsupporting
confidence: 93%
“…The pronounced group difference for multimodal TDT (figure 1) indicates dysfunction of the deep layer of the superior colliculus since cat models displayed enhanced neuron responses after multimodal compared to unimodal sensory stimuli 8 . Our results also support the findings of impaired spatial sensory processing in CD, since visual-tactile TDTs may at least partially represent spatial sensory integration 5 . As the superior colliculus is considered to be a key node for the discrimination of rapid changes in the environment and is also involved in the processing of visual stimuli 1 , it may explain the pronounced alterations of the visual and visual-tactile compared to tactile domains.…”
Section: Discussionsupporting
confidence: 90%
“…107 Despite the impressive number of papers that report reduced SICI in dystonia, several others have found it to be within the normal range (Table 1). 95,[108][109][110][111] Some discrepancies between studies could be the result of the large interindividual variability of SICI, which has only moderate reliability, 7,8 as well as subtle methodological differences. Nevertheless, despite its reduction, the role played by SICI in dystonia is still unclear.…”
Section: Variability In Motor Cortical Inhibitionmentioning
confidence: 99%
“…Reduced SICI has been reported in various forms of idiopathic dystonia, including focal hand dystonia, cervical dystonia, and fixed dystonia, [27][28][29][30][31][32][33][34][35][36][37] but other studies have reported normal SICI. 25,[38][39][40] Although SICI may be variable and absent in up to 13% of normal subjects, 41 the weight of evidence appears to favor a small reduction in SICI in dystonia. How this contributes to symptoms of dystonia is less clear.…”
Section: Motor Cortexmentioning
confidence: 99%
“…Only 2 studies have reported normal STDT in patients with cervical dystonia, possibly because of differences in the stimulating protocol adopted (randomized vs staircase protocol). 38,159 Although STDT has moderate intersubject variability in healthy subjects, there is some evidence that it has a fairly good discriminative power in between-group assessments 152,155,156 and yields reproducible values within subjects in multisession study designs. 143,153,158,160,161 Antelmi et al 142 provided evidence for the involvement of somatosensory inhibitory mechanisms in STDT.…”
Section: Sensory Abnormalitiesmentioning
confidence: 99%